Genotypes Selection on the basis of Periodic Performance - A Reliable Strategy to Maximize Crop Water Use Efficiency and Productivity in Arid Regions - Ihsan, Muhammad Zahid; El-Nakhlawy, Fathy Saad; Fahad, Shah; Alzamanan, Saleh (Annals of Arid Zone, 2017)
To evaluate drought resistance and adaptability of exotic wheat genotypes to rainfed conditions, a field experiment was performed at Arid Land Agriculture Research Station, King Abdulaziz University during 2012-13 and 2013-14 using randomized complete block design with split plot arrangement. Drought stress was applied as 100% and 50% of total water requirement in main plots while four wheat genotypes viz. Yocoro rojo (YR), Faisalabad (Fsd), Millat and F-50 were planted in sub plots. Drought stress significantly decreased crop growth, yield and yield components while increased water use efficiency, harvest index and stress susceptibility index, however the effect of genotypes was significant for all traits except harvest index. The Fsd throughout growth period presented higher values for leaf area index, dry matter accumulation. Moreover, maximum days to 50% maturity (93 d), water use efficiency (8.88 kg grain ha-1 mm-1), harvest index (28.79%), stress susceptibility index (1.23) and stress tolerance index (39%) were recorded for the Fsd. The drought tolerance potential of the genotype resulted in up to 21% increase in final grain yield under drought stress as compared to local genotype YR. Correlation analysis estimated the highest contribution of water use efficiency and stress indices towards genotype drought tolerance that translated in term of final grain yield. So, drought tolerant genotypes selection offered a reliable strategy to maximize crop water use productivity.